Determination of the Focus Strategies Related to Renewable Energy For Turkey by Using the Fuzzy Sectional SWOT - Adar, Elanur; Taşkan, Buşra; Karatop, Buket (My University, 2022)
Determining the strategies that Turkey need to focus at the renewable energy field is aimed in this study. For this, an integrated method called the Fuzzy Sectional SWOT consisting of the Fuzzy AHP and the Sectional SWOT methods was used. Some disadvantages of the traditional SWOT analysis are eliminated with the method used. Firstly, the renewable energy field was divided into 6 sub-sections (hyropower, solar, wind, biomass, hydrogen and geothermal) according to the logic of Sectional SWOT analysis. Then strengths, weaknesses, opportunities and threats for each of these sub-sections were determined using the Sectional SWOT analysis. Weights were found with the Fuzzy AHP method for each of the renewable energy sources and they were prioritized according to these weights. Finally, focus strategies related to renewable energy field for Turkey were obtained with the creation of strategies related to renewable energy sources. Consequently, the focus strategies which should be primarily addressed are related to use of renewable energy potential, social awareness about the renewable energy, government supports and incentives related to the renewable energy, selection of suitable areas for renewable energy plants and domestic production of the constituent parts of renewable energy plants.